PSYCHOSOCIAL REHABILITATION-COMPONENT FOR PROTECTION OF PERSONS WITH MENTAL DISABILITIES (Annual of the Faculty of Philosophy in Skopje, 2010)
The care for the mental health of the individuals with mental disabilities in community means organization of psychiatric services on efficient way in order to satisfy their needs from various aspects-psychiatric and psychosocial services, rehabilitation and easy access to the social integration.The significance of the component for protection of the persons with mental disabilities within the community is psychosocial rehabilitation. In contrast to the general definition of the concept rehabilitation, the strategy for the psychosocial rehabilitation should be oriented to the social skills of the patient and to mobilize the recourses of community. This approach will lead to the new area for researches, professional thinking for instance human and citizen’s rights, innovative legislation, closing of the psychiatric institu- tions/hospitals, flexibility of organization of the services for mental health, social inclusion of the people with mental disabilities, active measures and policies for living and employment.According to above mentioned, the psychosocial rehabilitation is not only a set of specific techniques, but it is innovative approach to the people with mental disabilities. The design of the strategic approach of the community will secure general modification in the attitude of whole society toward people with mental disabilities. The basic aim in this respect is optimal level of functionality of the individuals and society, in order to minimize the disabilities and handicaps and to create conditions for better, successful life in community.In this paper the ascent is given to questions related to the components for protection in community; dimensions of the psychosocial rehabilitation and specific measures in its realization.
Keywords: MENTAL HEALTH; PERSONS WITH MENTAL DISABILITIES; PROTECTION IN COMMUNITY; PSYCHOSOCIAL REHABILITATION